2020
DOI: 10.1101/2020.06.18.159491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global pleiotropic effects in adaptively evolvedEscherichia colilacking CRP reveal molecular mechanisms that define growth physiology

Abstract: Bacterial gene expression is governed by two synergistic mechanismsgrowth-rate dependent global machinery (e.g. ribosomes, RNA polymerase, metabolites and cofactors) and transcription factors that work together for optimal growth. However, in presence of glucose, coordination of global transcriptional regulator cAMP-CRP with such physiological resources, remain elusive.Here, we reveal that the deletion of CRP results in metabolic dysregulation with significant perturbation in protein biosynthesis machinery cou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 97 publications
(126 reference statements)
2
10
0
Order By: Relevance
“…The absence of CRP exhibited a growth defect in both exponential and stationary phases, as observed in Vibrio vulnificus ( Kim et al, 2013 ), E. coli ( Basak et al, 2014 ), K. pneumoniae ( Ou et al, 2017 ; Lin et al, 2018 ), and Haemophilus parasuis ( Jiang et al, 2020 ). These observations are in accordance with previous reports that explain how growth fitness is affected by the crp deletion, which produces fluctuations of metabolic gene expression and alterations of carbon metabolites, α-ketoacids, cAMP, and amino acids that promote proper coordination of protein biosynthesis machinery during metabolism ( Klumpp et al, 2009 ; Berthoumieux et al, 2013 ; You et al, 2013 ; Pal et al, 2020 ). CRP is a central regulator of carbon metabolism and has been implicated as an important facilitator of host colonization and virulence in many bacterial pathogens, including K. pneumoniae ( Xue et al, 2016 ; Lin et al, 2018 ; Panjaitan et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…The absence of CRP exhibited a growth defect in both exponential and stationary phases, as observed in Vibrio vulnificus ( Kim et al, 2013 ), E. coli ( Basak et al, 2014 ), K. pneumoniae ( Ou et al, 2017 ; Lin et al, 2018 ), and Haemophilus parasuis ( Jiang et al, 2020 ). These observations are in accordance with previous reports that explain how growth fitness is affected by the crp deletion, which produces fluctuations of metabolic gene expression and alterations of carbon metabolites, α-ketoacids, cAMP, and amino acids that promote proper coordination of protein biosynthesis machinery during metabolism ( Klumpp et al, 2009 ; Berthoumieux et al, 2013 ; You et al, 2013 ; Pal et al, 2020 ). CRP is a central regulator of carbon metabolism and has been implicated as an important facilitator of host colonization and virulence in many bacterial pathogens, including K. pneumoniae ( Xue et al, 2016 ; Lin et al, 2018 ; Panjaitan et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the biological roles of the most affected operons in the TTHB099-deficient strain were involved in metabolic pathways that have been reported to be regulated by the archetype CRP Ec [31]. For example, ribosome related genes were downregulated in the absence of TTHB099, similar to what Pal et al reported for their evolutionary expressed CRP Ec -deficient strains [32]. Likewise, iron transport genes were downregulated in the absence of TTHB099, similar to what was observed in the absence of CRP Ec , as Zhang et al reported [33].…”
Section: Discussionsupporting
confidence: 75%
“…7 ), limiting the potential of the system to attain a growth rate similar to that of the WT ( 12 , 53 55 , 57 ). Overall, in the absence of global regulators, we propose that the balance between growth rate and glucose uptake rate is attenuated, making the organism incapable to attain a fitter phenotype, unless forced upon a selection pressure ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, this delineated the complementary role of global transcriptional regulators with growth rate-dependent global machinery, predominant in exponentially growing cells. Such analyses can be extended to other global regulators such as cAMP receptor protein (CRP) ( 11 , 59 , 61 ), HNS ( 60 ), Lrp ( 62 ), and Fis ( 63 ), which tempts us to anticipate similar underlying mechanisms of regulation, presumably not confined only to glucose fermentative metabolism.…”
Section: Discussionmentioning
confidence: 99%